American cutaneous leishmaniasis: use of a skin test as a predictor of relapse after treatment - Valéria M.A. Passos; Sandhi M. Barreto; Alvaro J. Romanha; Antoniana U. Krettli; Ângela C. Volpini; Maria Fernanda F. Lima e Costa (The World Health Organization, 2000)
While relapses following clinical cure of American cutaneous leishmaniasis are frequent, no test has been described until now to predict such relapses. A cohort of 318 American cutaneous leishmaniasis patients was followed up for two years after treatment with meglumine antimoniate, during which time 32 relapses occurred, 30 in the first year and two in the second (accumulated risk: 10.5%). No association was found between these relapses and the parasite-specific antibody response before and after treatment, or between the relapses and stratification by sociodemographic and clinical characteristics. However when Leishmania was used as antigen, patients with a negative skin test at the time of diagnosis presented a 3.4-fold higher risk (hazard risk = 3.4; 95% confidence interval, 1.7-7.0) of American cutaneous leishmaniasis relapse, compared with patients with a positive response. This result shows that the skin test can be a predictor of American cutaneous leishmaniasis relapse after treatment.